Leadership Styles and Work–Life Balance as Predictors of Employee Engagement: A Case Study of a QSR Outlet in Denpasar - Ni Putu Ardriyani Tiara Wiratningsih; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Komang Oka Permadi (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
In service industries in particular, engagement among workers is critical to the success and longevity of any firm. On the other hand, a lack of staff involvement is still a problem for many businesses, which can have an impact on output and customer satisfaction. We hope to learn more about how work-life balance, innovative leadership, and transactions leadership influence engagement in this Denpasar QSR Outlet. Primary data for the study came from questionnaires given to all 113 employees using a saturation sample technique; the methodology was quantitative. Using SPSS-assisted multiple linear regression analysis, we looked at the data. The results demonstrate that transformational leadership positively affects employee engagement, as leaders who offer inspiration, motivation, and individualized attention can strengthen employees' emotional connection to their work. Transactional leadership also shows a positive effect, indicating that clear goals, rewards, and feedback can strengthen employees’ involvement in organizational activities. Moreover, work-life balance significantly enhances employee engagement, indicating that those who successfully manage their professional and personal lives exhibit greater enthusiasm and commitment in the workplace. This study's originality resides in the concurrent analysis of leadership styles and work-life balance within the fast-food restaurant sector, offering contemporary empirical evidence to aid managerial decision-making in enhancing employee engagement.